2015
DOI: 10.1186/s12889-015-1610-z
|View full text |Cite
|
Sign up to set email alerts
|

Hidden voices: prevalence and risk factors for violence against women with disabilities in Nepal

Abstract: BackgroundThere is an increasing body of evidence on the extent and predictors of violence against women in Nepal. However, much of the published research does not yet take into account additional features of marginalization and vulnerability suffered by some women – for example, women socially excluded on account of their disability. Critical gaps exist in empirical data on the extent, risk factors, access to care, socio-economic and health consequences of violence among women with disabilities in Nepal. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 5 publications
5
47
0
Order By: Relevance
“…A 2015 study with 475 Nepalese women living with a disability found that 57.7% reported experiencing lifetime emotional, physical or sexual violence, of whom 39% reported violence perpetrated by husbands. 8 In this sample, women living with disabilities who were younger, without children, employed and lacking autonomy in reproductive healthcare decisions experienced more violence. In another smaller scale report, 15 out of 20 blind women in Kathmandu reported experiencing some form of sexual abuse perpetrated by friends, family members or teachers.…”
Section: Introductionmentioning
confidence: 84%
“…A 2015 study with 475 Nepalese women living with a disability found that 57.7% reported experiencing lifetime emotional, physical or sexual violence, of whom 39% reported violence perpetrated by husbands. 8 In this sample, women living with disabilities who were younger, without children, employed and lacking autonomy in reproductive healthcare decisions experienced more violence. In another smaller scale report, 15 out of 20 blind women in Kathmandu reported experiencing some form of sexual abuse perpetrated by friends, family members or teachers.…”
Section: Introductionmentioning
confidence: 84%
“…Factors associated with domestic violence that have previously been documented were mostly from countries in Asia and Latin America with varying political, economic and cultural differences and very little focus on sub-Saharan Africa [ 5 , 9 , 12 , 19 21 ]. These factors reported in other countries may not necessarily lead to an increase in the likelihood of a Ghanaian woman’s risk of domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…Even in schools, research has shown that 14 and 52 % of girls are victims of sexual abuse and gender-based violence respectively [ 8 ]. These estimates may be far less than what actually persists, as violence against women and girls remain a largely hidden problem (sensitive issue) that only few females have the courage to openly confess [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rural Vietnam, Vung et al ( 2009 ) found that women who experienced IPV do not seek care unless they are suffering from severe physical injuries; the authors attribute this, in part, to the belief that IPV is a domestic matter that should not be shared with health workers or other public institutions. Similarly, in Nepal, cultural attitudes proscribe disclosure of IPV experiences, and the majority of women do not seek care or support (Puri et al 2015 ). In a study of behavioral scenario responses to IPV among former child soldiers in Nepal, only 31% of young women endorsed seeking family support, and 23% suggested reporting IPV to the police (Kohrt & Bourey, 2016 ).…”
Section: Discussionmentioning
confidence: 99%